Association of Tissue Transglutaminase Antibody Titer with Duodenal Histological Changes in Children with Celiac Disease - Hasan Hawamdeh; Basim Al-Zoubi; Yasameen Al Sharqi; Ayman Qasrawi; Yousef Abdelaziz; Maha Barbar (Gastroenterology Research and Practice)
Celiac disease is usually diagnosed by demonstrating gluten enteropathy in small bowel biopsy. Celiac specific antibodies are used as an initial screening test. The goal of this study is to test the relationship of the anti-tTG titer and severity of histological changes in Jordanian children with celiac disease. Method. The medical records of 81 children who had elevated anti-tTG titer and had duodenal biopsies available were retrospectively reviewed. Result. Assessing the association of anti-tTG titer with duodenal histopathological changes, 94% of those with high anti-tTG titer (≥180 U/mL) had histological evidence of celiac disease. There was statistically significant positive association between high anti-tTG titer and Marsh grading as 82% of patients with Marsh III had high anti-tTG titer (Chi2 18.5; P value 0.00; Odds Ratio 8.5). The fraction of patients with Marsh III who were correctly identified as positive by anti-tTG titer ≥ 180 U/mL was high (sensitivity = 81.6). Moreover, the fraction of patients with anti-tTG titer ≥ 180 U/mL who had Marsh III was also high (positive predictive value = 78.4). Conclusion. Anti-tTG titer ≥ 180 U/mL had significant positive association with Marsh III histopathological changes of celiac disease.